2017
DOI: 10.14419/ijdr.v6i1.8604
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and perception of orthodontic treatment among dental students

Abstract: Introduction: Malocclusion is known to contribute overall health status, as well as affecting individual's psychosocial health. Aim: To establish knowledge, attitude and perception of orthodontics treatment among dental students of one of the dental college of M.P. Material & Method: A descriptive cross study was carried out among 300 undergraduate dental students of people dental academy Bhopal M.P. India. Each classroom of the participants were visited. Self-administered questionnaire were distributed to a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…10a, 10b and 10c questions were only considered if the response to question 10 was 'yes'. Study done on dental students and dental surgeons 11 showed dental students had good knowledge about the orthodontic treatment and had a positive attitude towards it. This result cannot be compared to the result of the present study as the sample population differs vastly in these two studies.…”
Section: Resultsmentioning
confidence: 98%
“…10a, 10b and 10c questions were only considered if the response to question 10 was 'yes'. Study done on dental students and dental surgeons 11 showed dental students had good knowledge about the orthodontic treatment and had a positive attitude towards it. This result cannot be compared to the result of the present study as the sample population differs vastly in these two studies.…”
Section: Resultsmentioning
confidence: 98%
“…Self-awareness and knowledge of individuals about orthodontics is of great importance and should not be underestimated in order to improve patient's quality of life as well as to achieve successful orthodontic treatment planning and promising results (31,34) . A survey investigating the amount of knowledge and attitude among a sample of Egyptian patients toward different aspects of malocclusion and orthodontic treatment will provide more insight for better planning to improve peoples' well-being in relation to dental and functional health as well as self-esteem (36) .…”
Section: Discussionmentioning
confidence: 99%
“…The main cause for the lack of orthodontic treatment for patients with malocclusion is the lack of information about the malocclusion and lack of awareness about the benefits of treatment (32)(33)(34) . The more aware the patients are of their dental problems and orthodontic treatments, the more will be their demand for a better quality of life and better co-operation during treatment (35)(36)(37)(38) . Therefore, a conducted survey to assess the knowledge and attitude of patients about orthodontics is beneficial for better understanding and hence better planning for increasing the level of knowledge and reaching a more relevant attitude for patients.…”
Section: Introductionmentioning
confidence: 99%
“…6 Riya Agrawal studied the knowledge, attitude and perception of orthodontics treatment among 300 undergraduate dental students and found that 30% had a strong positive attitude towards orthodontic treatment. 7 Disha D Kandi studied 215 dental students with malocclusion and concluded the reasons for their negative response towards orthodontic treatment. Among 215 dental students, 28.17% students believe orthodontic treatment as long duration treatment, 26.23% students have subjective fear about treatment, 21.78% avoid it because of pain during treatment, 13.36% of students neglected orthodontic treatment, 6.43% students feels orthodontic treatment expensive, 3.46% students avoid it because of fear of relapse.…”
Section: Discussionmentioning
confidence: 99%